Maternal Age and Prematurity are Factors Associated with the Incidence of BBLR in KH Hayyung Regional General Hospital, Selayar Island, Indonesia - Dewi Suci Hajar; Pudji Lestari; Euvanggelia Dwilda; Astika Gita Ningrum; Asdiyar (Universitas Airlangga, 2025)
This study aims to determine the factors associated with the incidence of Low Birth Weight at KH Hayyung Hospital, Selayar Islands, given the increasing number of BBLR cases, and to use a quantitative case-control design. The sample consisted of babies born at KH Hayyung Hospital, Selayar Islands, who were selected purposively, resulting in a total of 50 samples. The research instrument was secondary data from patient medical records. The research data were analyzed using the chi-square test. The case group consisted of infants with a Birth Weight of less than 2500 g, while the control group consisted of infants with a Birth Weight of greater than 2500 g. Data were obtained from medical records throughout 2023 at KH Hayyung Hospital. Crosstabs were performed on the variables of education (no schooling, low, high), maternal age (at risk, not at risk), parity (primi and multi), and prematurity (term, premature), collected through purposive sampling. There were 25 cases and 25 controls with differences in the variables of education and parity which did not have a significant relationship to the incidence of Low Birth Weight at KH Hayyung Hospital in 2023 with a value of ρ>0.05 which means that there is no significant relationship, while the variables of maternal age and prematurity (ρ <0.05) had a substantial relationship to the incidence of Low Birth Weight at KH Hayyung Hospital in 2023. So, what is associated with the incidence of Low Birth Weight at KH Hayyung Hospital, Selayar Islands, in 2023 is the mother's age and prematurity.